Strategi Efektif untuk Meningkatkan Kemampuan Literasi Matematika - Junarti Junarti; M. Zainudin (Jurnal Pendidikan Edutama, 2022)
Abstract: The mathematics literacy of Indonesian students is still low. A mathematical literacy method is required to increase mathematical literacy skills. Several national and international articles have investigated various mathematical literacy strategies. As a result, the goal of this research is to present numerous mathematical literacy practices based on a review of 16 national and international studies. Data collection methods include identifying, analyzing, categorizing, classifying, and describing mathematical literacy strategies from four national and twelve international articles. The findings revealed that the types of mathematical literacy practices employed varied and did not differ between school levels. Elementary schools employ four4 types of strategies, secondary schools employ eleven11 strategies, and higher education employs 29 strategies. The content/literacy/notation area vocabulary strategy is widely utilized at three levels of education. PMRI is an approach utilized at two levels of education: primary school and secondary school. At the high school and university levels, the strategies used are connection, elaboration, control, understanding, consolidation, and visual representation. The effectiveness of the strategies discussed in these 16 articles was not evaluated specifically. The employment of strategies cannot be done in separately, but must be combined with other strategies. So multi-strategy is an effective and recommendable strategy.Keyword: effective strategy, mathematical literacy skills. Abstrak Kemampuan literasi matematika siswa Indonesia masih rendah. Strategi literasi matematika dibutuhkan untuk meningkatkan kemampuan literasi matematika. Beberapa strategi literasi matematika banyak dikaji pada beberapa artikel nasional maupun internasional. Oleh karena itu tujuan kajian ini untuk mendeskripsikan beberapa strategi literasi matematika dari kajian pustaka 16 artikel nasional dan internasional. Metode pengumpulaan data dengan mengidentifikasi, menganalisis, kemudian mengaktegorikan, mengklasifikasi serta mendeskripsikan strategi literasi matematika dari 4 artikel nasional dan 12 artikel internasional. Hasil penelitian menunjukkan jenis strategi literasi matematika yang digunakan variatif dan tidak membedakan tingkatan sekolah. Jumlah strategi yang digunakan di SD ada 4 jenis strategi, yang digunakan di Sekolah Menengah sebanyak 11 jenis strategi, dan yang digunakan di PT sebanyak 29 jenis strategi. Strategi yang sama dan banyak digunakan pada 3 tingkat pendidikan yaitu strategi kosakata area konten/ keaksaraan/ notasi. Strategi yang digunakan pada dua tingkat pendidikan sekolah dasar dan sekolah menengah seperti PMRI. Strategi yang digunakan pada tingkat sekolah menengah dan PT yakni seperti koneksi, elaborasi, kontrol, pemahaman, konsolidasi, dan representasi visual. Keefektifan strategi yang dikaji pada 16 artikel ini tidak dikaji secara spesifik. Penggunaan strategi tidak dapat dilakukan secara terpisah-pisah namun harus terintegrasi dengan beberapa strategi yang lainnya. Jadi strategi yang efektif dan dapat direkomendasikan yaitu multi-strategi.Kata kunci: strategi efektif, kemampuan literasi matematika